Tuning oxidizing, reducing, and redox characteristics via Fe, Co, and Ni incorporation in Pd-based halloysite-supported bimetallic core–shell three-way catalysts - Yun-Ting Wang; Wei-Jing Li; Yu-Hao Lin; Ming-Yen Wey; Kui-Hao Chuang (Fuel, 2026)

Schisandra chinensis polysaccharide attenuates diabetic islet cell injury by promoting autophagy via suppression of the PI3K/AKT/mTOR signaling cascade - Xiao-Ying Zhou; Guang-Hui Zhou; Wen-Chong Li; Jun-Feng Zhang; Ming-Kui Lin; Zi-Cong Liang; Rui-Ke Liu (Journal of Molecular Histology, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Steroidal saponins and homoisoflavonoids from the fibrous roots of ophiopogon japonicus and their anti-pulmonary fibrosis activities - Hang-Yi Pu; Yu Cao; Xi-Lang Jiang; Lin-Han Yang; Ming-Kui Wang; Fei Wang; Lun Wang (Natural Product Research, 2025)

A Cysteinyl-tRNA Synthetase Mutation Causes Novel Autosomal-Dominant Inheritance of a Parkinsonism/Spinocerebellar-Ataxia Complex - Han-Kui Liu; Hong-Lin Hao; Hui You; Feng Feng; Xiu-Hong Qi; Xiao-Yan Huang; Bo Hou; Chang-Geng Tian; Han Wang; Huan-Ming Yang; Jian Wang; Rui Wu; et al. (Neuroscience Bulletin, 2024)
This study aimed to identify possible pathogenic genes in a 90-member family with a rare combination of multiple neurodegenerative disease phenotypes, which has not been depicted by the known neurodegenerative disease. We performed physical and neurological examinations with International Rating Scales to assess signs of ataxia, Parkinsonism, and cognitive function, as well as brain magnetic resonance imaging scans with seven sequences. We searched for co-segregations of abnormal repeat-expansion loci, pathogenic variants in known spinocerebellar ataxia-related genes, and novel rare mutations via whole-genome sequencing and linkage analysis. A rare co-segregating missense mutation in the CARS gene was validated by Sanger sequencing and the aminoacylation activity of mutant CARS was measured by spectrophotometric assay. This pedigree presented novel late-onset core characteristics including cerebellar ataxia, Parkinsonism, and pyramidal signs in all nine affected members. Brain magnetic resonance imaging showed cerebellar/pons atrophy, pontine-midline linear hyperintensity, decreased rCBF in the bilateral basal ganglia and cerebellar dentate nucleus, and hypo-intensities of the cerebellar dentate nuclei, basal ganglia, mesencephalic red nuclei, and substantia nigra, all of which suggested neurodegeneration. Whole-genome sequencing identified a novel pathogenic heterozygous mutation (E795V) in the CARS gene, meanwhile, exhibited none of the known repeat-expansions or point mutations in pathogenic genes. Remarkably, this CARS mutation causes a 20% decrease in aminoacylation activity to charge tRNA Cys with L-cysteine in protein synthesis compared with that of the wild type. All family members carrying a heterozygous mutation CARS (E795V) had the same clinical manifestations and neuropathological changes of Parkinsonism and spinocerebellar-ataxia. These findings identify novel pathogenesis of Parkinsonism-spinocerebellar ataxia and provide insights into its genetic architecture.

Analyzing the correlation between quinolone-resistant Escherichia coli resistance rates and climate factors: A comprehensive analysis across 31 Chinese provinces - Yi-Chang Zhao; Zhi-Hua Sun; Ming-Xuan Xiao; Jia-Kai Li; Huai-yuan Liu; Hua-Lin Cai; Wei Cao; Yu Feng; Bi-Kui Zhang; Miao Yan (Environmental Research, 2024)

Discovery of the large-scale Eocene Xiwu Pb–Zn–Ag deposit in the Tethyan Himalaya: Geochronology, geochemistry, and C–H–O–S–Pb–Sr–Nd isotopes - Hua-Wen Cao; Qiu-Ming Pei; Xiao Yu; M. Santosh; Guang-Ming Li; Lin-Kui Zhang; Hao Zou; Lei Dong; Ke Gao; Zuo-Wen Dai; Jin-Biao Ai; Shuang-Shuang Lan; et al. (Gondwana Research, 2023)

Epitomizing biohydrogen production from microbes: Critical challenges vs opportunities - Jia Min Woon; Kuan Shiong Khoo; Asla A. AL-Zahrani; Meznah M. Alanazi; Jun Wei Lim; Chin Kui Cheng; Nurul Tasnim Sahrin; Fatima Musa Ardo; Sun Yi-Ming; Kuen-Song Lin; John Chi-Wei Lan; Md Sohrab Hossain; et al. (Environmental Research, 2023)

The contribution of subliminal perceptions, dietary habits, and psychological traits to the perception of oral tingling and burning sensations - Lu-lu Zhang; Chao Ma; Hou-yin Wang; Ying-ming Zheng; Qing-bin Zhang; Kui Zhong; Bo-lin Shi; Lei Zhao (Food Research International, 2023)

Stilbenes with potent cytotoxicity from the seedcases of Paeonia suffruticosa Andrews - Meng-Yue Yang; Zhao-Xiang Shao; Yue-Tong Wang; Yong-Lian Hou; Ding-Kang Zhu; Sha Chen; Ya-Hui Zhang; Fei Cao; Yong-Kui Jing; Bin Lin; Zhan-Lin Li; Da-Hong Li; et al. (Phytochemistry, 2023)

Endothelial cells induce degradation of ECM through enhanced secretion of MMP14 carried on extracellular vesicles in venous malformation - Gao-Hong Chen; Jie-Gang Yang; Hou-Fu Xia; Lin-Zhou Zhang; Yin-Hsueh Chen; Kui-Ming Wang; Xu Duan; Lian-Zhi Wu; Yi-Fang Zhao; Gang Chen (Cell and Tissue Research, 2022)

A new triterpene diglycoside from the roots of Bupleurum chinense DC. and its inhibitory effect on adipogensis in 3T3-L1 cells - Yujing Feng; Zhou-Wei Wu; Yanyan Luo; Liang Chen; Yufeng Cao; Lun Wang; Aftab Yaseen; Bin Chen; Ashfaq Ahmad Khan; Ming-Kui Wang; Guo-Lin Zhang; Xin-Feng Wang; et al. (Medicinal Chemistry Research, 2019)

Differences in functional activity between boys with pure oppositional defiant disorder and controls during a response inhibition task: a preliminary study - Yan Zhu; Kui Ying; Ji Wang; Linyan Su; Jingyuan Chen; Fan Lin; Dongyang Cai; Ming Zhou; Daxing Wu; Courtney Guo; Shi Wang (Brain Imaging and Behavior, 2014)

A new indole alkaloidal glucoside from the aerial parts of Clematis terniflora DC. - Wen-Ting Li; Bing-Xian Yang; Wei Zhu; Ming-Hua Gong; Xiang-Dong Xu; Xiang-Hong Lu; Lian-Li Sun; Jing-Kui Tian; Lin Zhang (Natural Product Research, 2013)

Transcriptional responses of maize seedling root to phosphorus starvation - Hai-Jian Lin; Jian Gao; Zhi-Ming Zhang; Ya-Ou Shen; Hai Lan; Li Liu; Kui Xiang; Maojun Zhao; Shufeng Zhou; Yong-Zhong Zhang; Shi-Bin Gao; Guang-Tang Pan (Molecular Biology Reports, 2013)

Mechano growth factor (MGF) promotes proliferation and inhibits differentiation of porcine satellite cells (PSCs) by down-regulation of key myogenic transcriptional factors - Li-Li Qin; Xiao-Kui Li; Jian Xu; De-Lin Mo; Xiong Tong; Zhi-Cheng Pan; Jia-Qi Li; Yao-Sheng Chen; Zhe Zhang; Chong Wang; Qiao-Ming Long (Molecular and Cellular Biochemistry, 2012)

Streptomyces shenzhenensis sp. nov., a novel actinomycete isolated from mangrove sediment - Huo Hu; Hai-Peng Lin; Qingyi Xie; Lei Li; Xin-Qiang Xie; Ming Sun; Kui Hong (Antonie van Leeuwenhoek, 2011)